Engineering Gel-Based Precursors into Advanced ORR Catalysts for Zn–Air Batteries and Fuel Cells: Insights into Hydrogels, Aerogels, Xerogels, Metal–Organic Gels, and Metal Aerogels - Shaik Gouse Peera; Myunghwan Byun (Gels, 2025)
Efficient electrocatalysts for the oxygen reduction reaction (ORR) are essential for numerous energy storage and conversion systems, including zinc–air batteries and fuel cells. Cutting-edge Pt/C catalysts remain the most efficient ORR catalysts to date; however, their high cost and inadequate stability impede their use in commercial devices. Recently, transition metal-based electrocatalysts are being pursued as ideal alternatives for cost-effective and efficient materials with a promising future. This review provides an in-depth analysis of the principles, synthesis, and electrocatalytic assessment of noble metal and transition metal-based catalysts derived from diverse gel precursors, including hydrogels, aerogels, xerogels, metal–organic gels, and metal aerogels. Electrocatalysts derived from gel precursors have garnered significant interest due to their superior physicochemical properties, including an exceptionally high surface area, adjustable porosity, adaptability, and scalability. Catalysts obtained from gel precursors offer numerous advantages over conventional catalyst synthesis methods, including the complete utilization of precursors, precise control over surface area and porosity, and uniform distribution of ORR active sites. Among the various types, metal aerogels are distinguished as the superior catalysts, exceeding the Department of Energy’s (DoE) 2025 targets for the mass and specific activities of ORR catalysts. In contrast, hydrogel- and aerogel-derived catalysts excel in terms of ORR activity, specific surface area, and the potential to incorporate high loadings of single-atom catalysts composed of transition metals. Ultimately, we unequivocally categorized the electrocatalysts into high-, moderate-, and low-performance tiers, identifying the most promising catalyst candidate within each gel classification. Concluding insights, future outlooks, and recommendations were provided for the advancement of cost-effective, scalable electrocatalysts derived from gels for fuel cells and zinc–air batteries.